Pengaruh Locus Of Control Terhadap Tindakan Kecurangan Dalam Pengadaan Barang Dan Jasa Di Bawah Tekanan Ketaatan - Eva Herianti (Universitas Muhammadiyah Jakarta, 2021)
This study to examine and analyze the effect of locus of control on fraudulent procurement of goods/services in conditions of obedience pressure. The experimental method used by researchers with participants is the Accounting Student, University of Muhammadiyah Jakarta. The type of data analysis used Two-Way Anova and One-Way Anova. The findings show that locus of control affects the occurrence of fraudulent procurement of goods/services in conditions of obedience pressure, in conditions of obedience pressure, external locus of control affects the occurrence of fraudulent procurement of goods/services compared to internal locus of control, and external locus of control affects the occurrence of fraudulent procurement of goods/services in a condition where there is obediece pressure compared to the absence of obedience pressure.